Students’ Perception of the Intensity on Audio Exposure in English Language Acquisition Among University - Sumarni; Syarifuddin Dollah; La Sunra (Universitas Islam Negeri Palopo, 2026)
Language acquisition plays an important role in developing English proficiency, particularly in pronunciation and listening skills. In recent years, digital tools such as Google Translate have been increasingly used by students as a self-directed learning resource to support pronunciation practice through audio exposure. However, limited studies have examined how the intensity of audio exposure influences students’ language acquisition in autonomous learning contexts. This study therefore investigates university students’ perceptions of the intensity of audio exposure using Google Translate and its contribution to English language acquisition. This research employed a qualitative descriptive approach involving eight third-semester students of the English Language Program at Universitas 17 Agustus 1945 Samarinda. Data were collected through structured questions using Google Forms followed by in-depth interviews conducted via Zoom. The data were analyzed thematically based on four categories: motivation and context of use, usage patterns and frequency, learning reflections and difficulties, and students’ recommendations. The findings indicate that intensive exposure to Google Translate audio helps students improve their pronunciation and develop independent learning strategies. Students reported that repeated listening, imitation, and self-recording activities supported their confidence and pronunciation accuracy. Despite some limitations, such as the monotone voice and rapid speed of the audio, students perceived the tool as beneficial for autonomous pronunciation practice. The study highlights the importance of integrating audio-based digital tools to support self-directed language learning in higher education.